The associations of parental smoking, quitting and habitus with teenager e-cigarette, smoking, alcohol and other drug use in GUI Cohort ’98 - Salome Sunday; Luke Clancy; Joan Hanafin (Scientific Reports, 2023)
Abstract We analyse parental smoking and cessation (quitting) associations with teenager e-cigarette, alcohol, tobacco smoking and other drug use, and explore parental smoking as a mechanism for social reproduction. We use data from Waves 1–3 of Growing Up in Ireland (Cohort ’98). Our analytic sample consisted of n = 6,039 participants reporting in all 3 Waves. Data were collected in Waves 1 and 2 when the children were 9 and 13 years old and in Wave 3 at age 17/18 years. Generalized Estimating Equations (GEE) models were used to analyse teenage substance use at Wave 3. Parental smoking was associated with significantly increased risk of all teenage substance use, adjusted odds ratios were aOR2.13 (ever e-cigarette use); aOR1.92 (ever alcohol use); aOR1.88 (current alcohol use); aOR1.90 (ever use of other drugs); aOR2.10 (ever-smoking); and aOR1.91 (current smoking). Primary caregiver smoking cessation (quitting) was associated with a lower risk for teenager current smoking aOR0.62, ever e-cigarette use aOR 0.65 and other drug use aOR 0.57. Primary caregiver smoking behaviour had greater associations than secondary, and age13 exposure more than age 9. Habitus seems to play a role and wealth was protective for teenage smoking. The findings suggest that prevention interventions should target both caregivers and their children.